Evaluation of Egg Quality Indices, Fertility, Hatchability % and Some Biochemical Parameters under the Effect of Some Environmental Stressors in Laying Hen - Ghanem , H.M.; Manaa, E.A.; Saleh, R.M. (International Journal of Poultry Science, 2017)
Objective: The aim of the present study was to investigate the effect of some environmental stressors (temperature and humidity) on egg quality indices, fertility and hatchability % and some biochemical data in laying hen. Materials and Methods: One hundred and eighty adult laying hens at 20 weeks of age were selected and used in this current experiment. The birds were randomly divided into three groups of 60 each and each group was further divided into five replicates of 12 birds. Three stages of thermal comfort values were established such as: Normal